2023
DOI: 10.3390/en16155732
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Methods for Analysis and Optimization of CHP Cogeneration Units Based on Landfill Biogas as a Progress in Improving Energy Efficiency and Limiting Climate Change

Krzysztof Gaska,
Agnieszka Generowicz,
Anna Gronba-Chyła
et al.

Abstract: Combined heat and power generation is the simultaneous conversion of primary energy (in the form of fuel) in a technical system into useful thermal and mechanical energy (as the basis for the generation of electricity). This method of energy conversion offers a high degree of efficiency (i.e., very efficient conversion of fuel to useful energy). In the context of energy system transformation, combined heat and power (CHP) is a fundamental pillar and link between the volatile electricity market and the heat mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In Europe, biogas recovered from landfill sites accounts for approximately 17% [50]. The essential parameters of biogas as a fuel include elemental composition, calorific value, minimum demand for air for combustion, flammability, and methane number values [51]. An organised collection of biogas from landfills results in reduced emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, biogas recovered from landfill sites accounts for approximately 17% [50]. The essential parameters of biogas as a fuel include elemental composition, calorific value, minimum demand for air for combustion, flammability, and methane number values [51]. An organised collection of biogas from landfills results in reduced emissions.…”
Section: Introductionmentioning
confidence: 99%
“…A key element when designing and selecting a site for a renewable energy investment is the type of energy source used. This mainly concerns the selection of the location of a given investment and, in particular, its inconvenience to the environment (biogas plants, landfills, wind power plants), the diversity of construction works (hydroelectric plants, high enthalpy geothermal, biomass boiler plants), the complexity of technological processes (biogas-tobiomethane conversion), or the required surface area and proper land (photovoltaic, wind farms) [Ligus, 2017;Gaska et al, 2023]. With the above in mind, access to selected geospatial data for the selected location and the relationships between them are crucial [Kochanek, 2015, Litwin et al, 2022 when planning and designing a RES structure such as a photovoltaic farm [Piotrowska-Woroniak, 2015; Knutel et al, 2020; https://ieo.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [47], a procedure for optimizing a CHP source fired with landfill biogas was presented. The results showed that waste fuel can be used in this way, and therefore additional reductions in CO 2 emissions can be made to the benefit of the natural environment.…”
Section: Introductionmentioning
confidence: 99%